Your sign to screen for prediabetes: a communications campaign to combat prediabetes amongst young sedentary working adults in Singapore - Ang, Amanda Hui Ting (Nanyang Technological University, 2023)
Your Sign to Screen for Prediabetes was an integrated communications campaign that tackled the issue of prediabetes among sedentary working adults aged 20 to 39 in Singapore between 21 November 2022 and 15 March 2023. While it is a reversible precursor to the incurable type 2 diabetes, prediabetes is asymptomatic, resulting in 50% of people in Singapore with the condition being unaware that they have it. This is an issue as detection is the first step in reversing it and preventing it from progressing on to diabetes. As such, the campaign helped working adults, who are at risk of prediabetes due to their sedentary work lifestyles but lack access to subsidised screening programmes, to spot signs in their lives that they should screen for prediabetes. The Health Belief Model guided the qualitative and quantitative research, campaign strategy and executions like an integrated media treasure hunt, a screening drive which accommodated the hectic schedules of the audience and social media advertising. To measure results, comparisons of composite index mean scores and two-tailed independent samples t-tests were conducted among groups exposed and unexposed to the campaign. The exposed group reported significantly higher scores in prediabetes knowledge (7.15%), intention to have healthy diets (12.42%), engage in physical activity (7.40%) and attend screenings (19.22%). Further, the campaign provided 101 fully-subsidised prediabetes screenings and garnered public relations (PR) value worth $109,320, including an endorsement by the Minister of State for Culture, Community and Youth.